2020
DOI: 10.1002/jnr.24628
|View full text |Cite
|
Sign up to set email alerts
|

Can fructose influence the development of obesity mediated through hypothalamic alterations?

Abstract: Epidemiological data from the last decades point to an exponential growth in the number of obese people. Different behavioral factors, mainly associated with food consumption, appear to contribute significantly to its development. Concomitant with increased obesity rates, an increase in the consumption of fructose has been observed; therefore, fructose consumption has been implicated as an important obesogenic factor. However, changes in brain activity due to fructose consumption are possible, especially in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…These results led us to hypothesize that the fructose-associated gain of S-100B is a trigger event driving hypothalamic inflammation. It is worth mentioning that hypothalamic inflammation is considered a potential trigger for the deregulation of mechanisms involved in food control and energy metabolism [ 28 , 83 , 84 ]. As a matter of fact, a long-term fructose diet was reported to induce increased IL-6 and TNF-alpha expression in mice hypothalamus, together with down-regulation of the expression of both the anorexigenic proopio-melanocortin (POMC) and the orexigenic NPY [ 85 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results led us to hypothesize that the fructose-associated gain of S-100B is a trigger event driving hypothalamic inflammation. It is worth mentioning that hypothalamic inflammation is considered a potential trigger for the deregulation of mechanisms involved in food control and energy metabolism [ 28 , 83 , 84 ]. As a matter of fact, a long-term fructose diet was reported to induce increased IL-6 and TNF-alpha expression in mice hypothalamus, together with down-regulation of the expression of both the anorexigenic proopio-melanocortin (POMC) and the orexigenic NPY [ 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a matter of fact, a long-term fructose diet was reported to induce increased IL-6 and TNF-alpha expression in mice hypothalamus, together with down-regulation of the expression of both the anorexigenic proopio-melanocortin (POMC) and the orexigenic NPY [ 85 ]. As above mentioned, several animal studies demonstrated the orexigenic effect of fructose [ 28 ]. Indeed, long-term fructose feeding in rats was associated with increased expression of the NPY gene [ 26 , 70 , 86 ], reduced POMC expression and impairment in the melanocortin system [ 26 ], and augmented gene expression of the agouti-related peptide [ 70 , 86 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Present Addresses: Vydiant Inc., Folsom, CA 95630, USA. 9 Present Address: CRCHU de Québec-Université Laval, Quebec City, Québec, Canada.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…Fructose metabolism and the consequent effects on the regulation of host energy balance have been extensively studied in the gastrointestinal tract, kidney, and liver [25,64]. Human, laboratory animal, and cell culture systems have also demonstrated that fructose can be metabolized in the hypothalamus [9], innate immune system [83], cardiac and skeletal muscles ( [25,64], and adipose tissue and cells [25,64]. Excess fructose intake leads to the development of the multiple features of metabolic syndrome [7] including fatty liver, insulin resistance, diabetes, obesity, and hypertension [25].…”
Section: Introductionmentioning
confidence: 99%